SEARCH FOR W-BOSON PAIR PRODUCTION IN P(P)OVER-BAR COLLISIONS AT ROOT-S=1.8 TEV - Abachi, S; Abbott, B; Abolins, M; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Aihara, H; Alitti, J; Alvarez, G; Alves, G; et al. (1995)
The results of a search for W boson pair production in pp» collisions at s=1.8 TeV with subsequent decay to dilepton (e,ee, and) channels are presented. One event is observed with an expected background of 0.56 0.13 events with an integrated luminosity of approximately 14 pb-1. Assuming equal strengths for the WWZ and WW gauge boson coupling parameters and, limits on the CP-conserving anomalous coupling constants are -2.6< <2.8 and -2.1< <2.1 at the 95% confidence level. © 1995 The American Physical Society.